Ontological Foundations of Bioethics from the Nicomachean Ethics (EN) Aristotle: an Analysis for Reflection - Díaz Sosa, Juan Arturo; Caligiore Corrales, Irene (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
The ontological foundations of bioethics are traced from the "Nicomachean Ethics" (EN) Aristotle. We analyze the "Biological Treaties", the "Treaties Psychological" and "Metaphysics" Aristotle latter being considered the seminal work of Western ontological thought. The "Midpoint" the "Prudence", "Justice", the Amistad, the "Act", the "Power", the "substance" and "Alma", respectively, are basic categories. The Spanish translation of the EN, by Marías, J. (1970), was the basis for interpretive contributions corresponding, analyzed by books reason of logical and systematic sequence of this work. Bioethics is assumed that since it implies deliberation prerequisite for formulating conclusions should be viewed as a tool for decision making. These decisions take transcendent nature they involve inherent addressing "Being" as "Being and" Being "in Society problems. For purposes of defining the present manuscript. The most significant findings related to the analysis of the Nicomachean Ethics (EN) Disclosed.